2021
DOI: 10.1371/journal.pntd.0009896
|View full text |Cite
|
Sign up to set email alerts
|

Ovitrap surveillance of dengue vector mosquitoes in Bandung City, West Java Province, Indonesia

Abstract: Larval surveillance is the central approach for monitoring dengue vector populations in Indonesia. However, traditional larval indices are ineffective for measuring mosquito population dynamics and predicting the dengue transmission risk. We conducted a 14-month ovitrap surveillance. Eggs and immature mosquitoes were collected on a weekly basis from an urban village of Bandung, namely Sekejati. Ovitrap-related indices, namely positive house index (PHI), ovitrap index (OI), and ovitrap density index (ODI), were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
0
23
0
3
Order By: Relevance
“…In Indonesia, control measures have been promoted through the 3M plus (covering, draining, and burying unused water containers) program as shown in the declining DHF incidence rate [ 39 , 40 ]. However, available data have indicated that mosquito populations remain high [ 41 ], so that pesticides are still commonly used as an alternative measure in mosquito control in many locations in Indonesia. Therefore, the experts agreed that it has a very low likelihood with a low consequence, which resulted in a negligible risk of severity level.…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, control measures have been promoted through the 3M plus (covering, draining, and burying unused water containers) program as shown in the declining DHF incidence rate [ 39 , 40 ]. However, available data have indicated that mosquito populations remain high [ 41 ], so that pesticides are still commonly used as an alternative measure in mosquito control in many locations in Indonesia. Therefore, the experts agreed that it has a very low likelihood with a low consequence, which resulted in a negligible risk of severity level.…”
Section: Discussionmentioning
confidence: 99%
“…For long-term vector surveillance, an ovitrap surveillance system is an alternative tool. Ovitrap is a user-friendly and effective tool for monitoring dengue vectors and is applied in various countries like Singapore, Australia, Indonesia (Sasmita et al, 2021). A lethal oviposition trap was used to attract gravid female mosquitoes, subsequently laying eggs.…”
Section: Genetic Diversitymentioning
confidence: 99%
“…Surveilans vektor khususnya dilakukan saat curah hujan mulai masuk pada bulan basah dengan menentukan distribusi, kepadatan populasi, habitat larva, dan faktor risiko spatiotemporal terkait penularan dengue. 46,47,48,49 Surveilans migrasi pada program malaria dapat diadopsi menjadi strategi untuk mengurangi risiko penularan DBD karena proses mobiliasi masyarakat. Surveilans ini merupakan sistem pencatatan, pelaporan, pemantauan dan evaluasi terhadap perpindahan (mobilitas penduduk) baik yang datang maupun pergi ke luar wilayah dan dilakukan secara terus menerus serta berkelanjutan.…”
Section: Pembahasanunclassified